Electrospun Nanofibers as Carriers of Microorganisms, Stem Cells, Proteins, and Nucleic Acids in Therapeutic and Other Applications - Stojanov, Spase; Berlec, Aleš (Frontiers in Bioengineering and Biotechnology, 2020)
Electrospinning is a technique that uses polymer solutions and strong electric fields to produce nano-sized fibers that have wide-ranging applications. We present here an overview of the use of electrospinning to incorporate biological products into nanofibers, including microorganisms, cells, proteins, and nucleic acids. Although the conditions used during electrospinning limit the already problematic viability/ stability of such biological products, their effective incorporation into nanofibers has been shown to be feasible. Synthetic polymers have been more frequently applied to make nanofibers than natural polymers. Polymer blends are commonly used to achieve favorable physical properties of nanofibers. The majority of nanofibers that contain biological product have been designed for therapeutic applications. The incorporation of these biological products into nanofibers can promote their stability or viability, and also allow their delivery to a desired tissue or organ. Other applications include plant protection in agriculture, fermentation in the food industry, biocatalytic environmental remediation, and biosensing. Live cells that have been incorporated into nanofibers include bacteria and fungi. Nanofibers have served as scaffolds for stem cells seeded on a surface, to enable their delivery and application in tissue regeneration and wound healing. Viruses incorporated into nanofibers have been used in gene delivery, as well as in therapies against bacterial infections and cancers. Proteins (hormones, growth factors and enzymes) and nucleic acids (DNA and RNA) have been incorporated into nanofibers, mainly to treat diseases and enhance their stability. To summarize, incorporation of biological products into nanofibers has numerous advantages, such as providing protection and facilitating controlled delivery from a solid form with a large surface area. Future studies should address the challenge of transferring nanofibers with biological products into practical and industrial use.